Ethambutol-related Impaired Visual Function in Childrens Less than 5 Years of Age Treated for a Mycobacterial Infection: Diagnosis and Evolution. Issue 4 (April 2015) - Levy, Michael; Rigaudière, Florence; de Lauzanne, Agathe; Koehl, Bérengère; Melki, Isabelle; Lorrot, Mathie; Faye, Albert
Abstract : Background: The effects of ethambutol (EMB) on vision are particularly difficult to detect in children less than 5 years of age because of a lack of complaints and objective clinical signs. The aim of this study was to assess the frequency of visual abnormalities and the utility of visual-evoked potentials (VEPs) recordings in monitoring the visual function of children less than 5 years of age who were exposed to EMB during anti-mycobacterial treatment. Methods: We performed a retrospective study in Robert-Debré University Hospital, Paris, France, including all children less than 5 years of age, who were treated with EMB for a mycobacterial infection from January 2002 to December 2012. Results: Fourteen patients were enrolled, including 12 treated for Mycobacterium tuberculosis infection. The sex ratio was 1:1. The median age was 1.65 years (0.3 to 4.7). Five patients had subarachnoid involvement. The median EMB dose was 22 mg/kg/day (15 to 27). Only 11 patients were monitored using VEPs. Three children (27.3%) developed a visual impairment secondary to EMB, with delays of 4, 7 and 36 weeks. One of the 3 patients developed an impairment of the retrochiasmatic visual pathways, and 2 other patients developed classical retrobulbar optic neuritis. In all cases, the discontinuation of EMB resulted in a normalization of these findings. Conclusion: Alterations in visual function related to the use of EMB are not uncommon in young children and are most likely underestimated. Systematic close monitoring using VEPs recordings is needed in young children treated with EMB. Abstract : Supplemental Digital Content is available in the text.